A novel TGM1 mutation, leading to multiple splicing rearrangements, is associated with autosomal recessive congenital ichthyosis (2015)
Summary Autosomal recessive congenital ichthyosis (ARCI) is a group of rare, clinically heterogeneous skin disorders that affect cornification. ARCI includes lamellar ichthyosis, congenital ichthyosiform erythroderma and harlequin ichthyosis. TGM1 mutations cause > 50% of ARCI cases in the USA. We report two siblings with ARCI. They were found to carry a novel aetiological TGM1 mutation, which leads to the synthesis of multiple abnormal transcripts. These molecules resulted from three independent mechanisms: intron retention, exon skipping and activation of expand cryptic splice sites. Taken together, our findings expand the known TGM1 mutation repertoire, and provide an insight into the molecular mechanisms leading to ARCI phenotypes. These results could be useful for genetic counselling and future potential genotype-phenotype correlations. © 2015 British Association of Dermatologists.